Studi Simulasi Reservoir pada Lapangan Shale Gas - Prima Adhi Surya; Ajeng Purna Putri Oktaviani (Jurnal Migasian, 2022)
Indonesia has potential shale gas reserves as much as 303 TCF. To maximize shale gas production, reservoir stimulation by hydraulic fracturing and injection may be needed. Furthermore, because shale gas reservoir is very complex, reservoir simulation needs to be performed to help produce gas trapped in the shale formation. This study provides process that is done to model shale gas field and observe desorption phenomenon in the reservoir during production phase. This study also performs N2 gas injection to analyze the effect of injecting the gas for reservoir performance. The number of simulations done in this study is four simulation scenarios. From all four shale gas reservoir simulations, cumulative production of methane gas, reservoir pressure, recovery factor, and cumulative of N2 gas that are produced back to the surface will be obtained. From the study it is shown that hydraulic fracturing, desorption phenomenon, and apparent permeability due to non-darcy fluid behavior becomes important in shale gas reservoir. Each simulation scenario has differences and shows that desorption phenomenon is more impactful to the reservoir performance in shale gas field. Simulation results also shows that N2 injection doesn’t significantly affect shale gas reservoir production performance.